The Determinants of Dividend Policy for Non-Financial Companies in Jordan - Jaara, Bassam; Alashhab, Hikmat; Jaara, Osama Omarali (International Journal of Economics and Financial Issues, 2018)
This research investigates the determinant of dividend policy for a sample of Non-financial companies in Jordan over the period 2005-2016. This study concentrates on some variables that effect the dividend pay-out ratio and the dividend yield such as: Company size, risk, investment opportunities, historical dividend, profitability and leverage. This study used the panel dataset of non-financial companies in Jordan. The results show that company size showed significant positive impact, which could solve the free cash flow problem, mature and large companies were paying more and consistent dividends. The ROE was positive and significant, that firms with high profitability were paying larger consistent dividend pay-outs. The impact of historical dividends always positive and significant and signposts that firms trend of dividend payout rather than the random paying. Risk has a negative impact on the payout levels. The analysis was depending on some theories that affect the dividend policy such as: Dividends Irrelevance Theory, bird in hand theory, pecking order theory, Agency problems and signaling theory. Keywords: Dividend Policy, Corporate Pay-out, Jordan JEL Classifications: G1, G3, G23